2006
DOI: 10.1099/vir.0.81423-0
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells pulsed with hepatitis C virus NS3 protein induce immune responses and protection from infection with recombinant vaccinia virus expressing NS3

Abstract: Infections with Hepatitis C virus (HCV) pose a serious health problem worldwide. In this study, the hypothesis that adoptive transfer of dendritic cells (DCs) pulsed with HCV NS3 protein and matured with an oligodeoxynucleotide (ODN) containing CpG motifs (CpG) ex vivo would initiate potent HCV-specific protective immune responses in vivo was tested. NS3 protein was efficiently transduced into DCs and treatment of DCs with CpG ODN induced phenotypic maturation and specifically increased the expression of CD40.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…These results suggest that BMDC incubation with aBNBD3 at 1,000 ng/ml, and to a lesser extent at 100 ng/ml, results in functional maturation and activation, as shown by their increased allostimulatory ability. Additionally, we observed from the dose-response curve, as did Yu et al (37), that a DC/responder cell ratio of 1:10 gave the best response in MLR assays (Fig. 6b).…”
Section: Functional and Biological Activities Of Synthesized Peptidessupporting
confidence: 51%
“…These results suggest that BMDC incubation with aBNBD3 at 1,000 ng/ml, and to a lesser extent at 100 ng/ml, results in functional maturation and activation, as shown by their increased allostimulatory ability. Additionally, we observed from the dose-response curve, as did Yu et al (37), that a DC/responder cell ratio of 1:10 gave the best response in MLR assays (Fig. 6b).…”
Section: Functional and Biological Activities Of Synthesized Peptidessupporting
confidence: 51%
“…Both in vitro and in vivo, several studies have demonstrated that DCs expressing HBV or HCV antigens induce antigen-specific CD4 + and CD8 + T cell responses 111 112 113 114. It is difficult, however, to study the experimental approaches of DC-based immunisation against HBV and HCV to terminate persistent infection in vivo, because the host range of HBV and HCV is limited to man and chimpanzees.…”
Section: Dcs As Targets and Tools For Antiviral Treatmentmentioning
confidence: 99%
“…DCs may initiate an antigen-specifi c T-cell response which is either immunogenic in the presence of or tolerogenic in the absence of an additional maturation stimulus. 75,76,88 Yu et al 87 observed that DCs following CpG ODN-induced maturation prior to inoculation were much more immunogenic than DCs with an immature phenotype.…”
Section: Dendritic Cell-based Vaccinationmentioning
confidence: 98%
“…Yu et al 87 employed DOTAP as a liposomal transfection reagent. Kuzushita et al 89 used Pep1, a short amphiphatic peptide carrier that delivers peptides and proteins into cells without denaturation or crosslinking, and Matsui et al 86 applied an anthrax toxinmediated antigen-delivery system.…”
Section: Dendritic Cell-based Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation